One of the most useful formulas of all time historically is the solution of the equation:
ax2 + bx + c = 0
The equation above is known as the quadratic equation.
Theorem: (-b ± √b2 – 4ac)/2a is the solution to the quadratic equation.
(1) First, we multiply both sides by 4a and get:
4a2x2 + 4abx + 4ac = 0
(2) Next, we add b2 – b2 to the equation:
4a2x2 + 4abx + b2 + 4ac – b2 = 0
(3) Now, we add b2 – 4ac to both sides which gives us:
4a2x2 + 4abx + b2 = b2 – 4ac
(4) Further, we know that:
(2ax + b)2 = 4a2x2 + 4axb + b2
(5) Combining #4 and #3, gives us:
(2ax + b)2 = b2 – 4ac
(6) Now, taking the square root of both sides gives us:
2ax + b = ±√b2 – 4ac
(7) Now, using basic algebra, we get to:
x = (-b ±√(b2 – 4ac))/2a.
Posted on Tuesday,July 3, 2012, in Quadratic equation and tagged basic algebra, equation, formula, polynomials of degree 2, quadratic equation, quadratic formula, square root. Bookmark the permalink. 1 Comment.